“Pulmonary and intestinal tuberculosis in a kidney transplant recipient”, about the paper by the authors R.O. Kantariya, A.V. Vatazin, A.B. Zulkarnayev, V.A. Stepanov from Moscow Regional Research and Clinical Institute n.a. M.F. Vladimirskiy, Moscow, Russia, published in Transplantologiya Journal No. 2, 2019 - M. M. Kaabak (Трансплантология (Москва))
Кантария Р.О., Ватазин А.В., Зулькарнаев А.Б., Степанов В.А. Туберкулез легких и кишечника у реципиента почечного трансплантата. Трансплантология. 2019;11(2):141–149. https://orcid.org/10.23873/2074-0506-2019-11-2-141-149